2022
DOI: 10.1155/2022/9188553
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining and Meta-Analysis of Psoriasis Based on Association Rules

Abstract: Psoriasis is a common chronic and recurrent disease in dermatology, which has a great impact on the physical and mental health of patients. Meta-analysis can evaluate the effectiveness and safety of defubao in the treatment of psoriasis vulgaris. This article observes psoriasis skin lesions treated with topical defubao and the changes in blood vessels under dermoscopy. Considering that the Apriori algorithm and the existing improved algorithm have the problems of ignoring the weight and repeatedly scanning the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Through the simulation test, the execution time of the improved Apriori algorithm was observably reduced, which indicated that the introduction of the interest-based model helped improve the running speed of the Apriori algorithm. Furthermore, the number of attribute items of the improved Apriori algorithm was smaller than that of the classical Apriori algorithm, which indicated that the introduction of the interest degree model was helpful to reduce the redundancy and space occupancy of the algorithm based on the guarantee of the accuracy and stability of the Apriori algorithm [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through the simulation test, the execution time of the improved Apriori algorithm was observably reduced, which indicated that the introduction of the interest-based model helped improve the running speed of the Apriori algorithm. Furthermore, the number of attribute items of the improved Apriori algorithm was smaller than that of the classical Apriori algorithm, which indicated that the introduction of the interest degree model was helpful to reduce the redundancy and space occupancy of the algorithm based on the guarantee of the accuracy and stability of the Apriori algorithm [ 20 ].…”
Section: Discussionmentioning
confidence: 99%